Measurement- and Simulated Annealing (SA) Optimization-Based Inductor Model Coupled to Chassis - Park, Junyong; Vahdani, Reza; Kim, DongHyun (IEEE transactions on instrumentation and measurement, 2025)
In automotive systems, a metal chassis protects the components against the external environment. However, the metal chassis is conductive, which results in unwanted conducted emission (CE) coupling to electric components. An inductor used for power factor correction (PFC) is one of the affected components. When the inductor is mated with the metal chassis, the impedance of the inductor changes. It is also hard to predict the CE coupling due to the structure-dependent characteristics. That is, the CE coupling is not negligible and hard to clarify. Therefore, this article proposes an efficient modeling method for the inductor, which is mated with the metal chassis. The proposed method includes the measurements and optimization algorithm. The measurement setups include an impedance analyzer (IA) and a vector network analyzer (VNA). The IA is used to measure the accurate inductance value of the inductor, and the VNA is used to measure the coupling to a chassis. The optimization algorithm includes simulated annealing (SA). The equivalent models for the inductor, the inductor with 2-D metal chassis, and the inductor with 3-D metal chassis are introduced, respectively. The introduced equivalent models are well-matched to the measurements up to 100 MHz.